Super-tough low-density steel medium plate and preparation method thereof

Through low Mn content design and two-stage multi-pass rolling process, a ferrite + martensite layered heterostructure is formed, which solves the problems of high density and insufficient low-temperature impact performance of traditional medium-thick plate materials in deep-sea environments, and achieves excellent comprehensive mechanical properties and improves welding performance.

CN119736556APending Publication Date: 2025-04-01UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202510030112.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional marine engineering medium and thick plate materials have high density in deep-sea environments, resulting in increased structural weight and insufficient low-temperature impact performance at low temperatures. There are technical difficulties in the welding process of high manganese design.

Method used

By designing ultra-tough low-density steel medium and thick plates with low Mn content, a two-stage multi-pass rolling process is adopted to form a layered heterostructure of ferrite + martensite, and the two-phase ratio is regulated through critical annealing to improve the comprehensive mechanical properties and welding properties of the materials.

Benefits of technology

It has achieved excellent impact work and comprehensive mechanical properties at low temperatures, reducing welding difficulty, saving production costs, and improving the low-temperature impact toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736556A_ABST
    Figure CN119736556A_ABST
Patent Text Reader

Abstract

The invention provides a super-tough low-density steel medium plate and a preparation method thereof, and belongs to the field of metal alloys. The alloy comprises the following components in percentage by weight: 0.008-0.33% of C, 1.5-5.5% of Al, 0.6-5.5% of Mn, 0.01-3.6% of Cr, 0.0015-0.32% of Ti, and the balance of Fe and inevitable impurities, wherein the content of C, Al and Mn meets the condition that Mn + Cr is more than or equal to 0.7 and less than or equal to 8.3, and the content of C, Al and Mn meets the requirement that Mn + Cr is more than or equal to 0.7 and less than or equal to 8.3. The Al-containing low-density steel with the two-phase region temperature range larger than or equal to 300 DEG C is obtained by regulating and controlling the content of C, Al and Mn through component design, a layered heterostructure with the microstructure being ferrite and martensite at the room temperature is obtained through two-stage multi-pass controlled rolling and controlled cooling, and the proportion of the two phases is regulated and controlled through critical annealing so that the thick plate can obtain super toughness. The yield strength of the thick plate is larger than or equal to 690 Mpa, the tensile strength is larger than or equal to 890 Mpa, the Charpy impact energy of the thick plate and a transverse V-opening sample at the temperature of-100 DEG C is larger than 220 J (continuous), and due to the compound addition of Al and Cr, the thick plate has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal alloys, and particularly relates to an ultra-tough low-density steel medium and thick plate. Background Art

[0002] With the growing global demand for the development of marine resources, the requirements for material performance in the marine engineering field are also getting higher and higher. Especially in deep-sea mining and offshore platform construction, there are strict requirements on the strength, corrosion resistance, pressure resistance and weight of structural materials. Although traditional marine engineering structural materials, such as carbon steel and stainless steel, have good mechanical properties, their density is relatively high in the deep-sea high-pressure environment, which leads to an increase in the overall structural weight, thereby increasing the construction and maintenance costs. Medium and thick plates, as an important material for marine engineering structural steel, are widely used in the construction of ships, platforms, pipelines and other structures. However, traditional medium and thick plate materials have some limitations. First, their high density leads to an increase in the overall weight of the structure in the deep-sea environment, which is not conducive to improving operational efficiency and economy. Secondly, these materials have limited corrosion resistance in seawater, and require frequent maintenance and replacement, which increases operating costs. In addition, with the expansion of marine engineering to deeper waters, higher requirements are placed on the low-temperature impact performance of materials. However, in order to reduce weight, a high content of Al is added to the material. The large amount of Al element deteriorates the mechanical properties of the material, especially the low-temperature impact performance. In order to improve the insufficient toughness of Al-containing steel, a large amount of C and Mn must be added to make the steel matrix obtain a large amount of austenite to improve it. However, the addition of a large amount of Mn causes many technical difficulties in the melting and welding of steel due to the volatilization of Mn vapor, and the addition of Mn will form coarse κ carbides in the matrix, deteriorating the material properties. In order to solve the above problems, the development of ultra-tough low-density medium and thick plates with medium and low manganese content has become a key technology and problem in the field of marine engineering materials.

[0003] Patent document CN107674955A discloses a chemical composition with the following mass percentages: Mn: 19.40-20%; Al: 9.82-10%; C: 0.98-1%; P≤0.003%; S≤0.003%, and the rest is Fe and unavoidable impurities. Through smelting, casting, hot rolling, solution treatment, cold rolling, annealing and cooling, a low-density steel with a multiphase structure of austenite + ferrite + κ carbide is obtained. The patent has a high Mn content, resulting in poor stability of the austenite structure; and the influence of grain boundary κ formation on performance cannot be avoided.

[0004] Patent document CN103820735A discloses a chemical composition with a mass percentage of: C: 0.28-1.15%, Al: 3.0-12.0%, Mn: 6.9-27.60%, Si: 0.01-2.0%, Cr: 0.01-0.80%, Ni: 0.01-0.60%, Mo: 0.01-0.30%, V: 0.001-0.10%, Nb: 0.001-0.06%, Ti: 0.001-0.02%, and the rest is Fe and unavoidable impurities. This patent only considers the effect of precipitation phase strengthening by adding a large amount of alloying elements, without considering the influence of precipitation on its toughness.

[0005] Patent CN202210463766.8 and Patent CN202210463745.6 have also developed a dual-phase low-density steel containing Al, but in order to obtain good toughness, a higher content of Mn element was added, and its microstructure is a dual-phase low-density steel of austenite, without considering the problems in its smelting and welding processes.

[0006] In summary, based on the existing research on low-density medium and thick plates for marine structures, it is urgent to develop a low-density medium and thick plate for marine engineering that has excellent comprehensive mechanical properties at low temperatures, especially low-temperature impact resistance, low Mn content, and good welding performance. Summary of the invention

[0007] The purpose of the present invention is to provide an ultra-tough low-density medium and thick plate and a preparation method thereof. The low-density medium and thick plate prepared by the present invention has excellent Charpy impact energy at low temperature and is suitable for structural steel in extreme marine environments. The present invention not only does not add microalloying elements, has a simple process and low production cost, but also improves the welding performance of the low-density medium and thick plate prepared by the present invention through a low Mn content design.

[0008] The present invention relates to a super-tough low-density steel medium and thick plate, whose chemical composition is recorded by weight percentage as C: 0.008-0.33%, Al: 1.5-5.5%, Mn: 0.6-5.5%, Cr: 0.01-3.6%, Ti: 0.0015-0.32%, and the content of C, Al, and Mn elements meets the following requirements: 0.7≤Mn+Cr≤8.3, the rest are Fe and unavoidable impurities.

[0009] The preferred chemical composition by mass percentage is: C: 0.009-0.31%, Al: 1.7-5.3%, Mn: 0.7-5.2%, Cr: 0.02-3.5%, Ti: 0.0018-0.31%, and the content of C, Al, and Mn elements meets the following requirements: 0.7≤Mn+Cr≤8.3, the rest are Fe and unavoidable impurities.

[0010] The specific steps of the above-mentioned method for preparing ultra-tough low-density steel medium and thick plates are as follows:

[0011] 1) Melting is carried out according to the alloy composition ratio, and the ingot is kept at 1190-1260°C for 90-300 minutes for homogenization treatment, and then rolling is started above the end austenitizing temperature.

[0012] 2) The rolling is divided into two stages and multiple passes, with 3 to 5 passes in each stage and the interval between passes being no more than 18s. The first stage is high temperature recrystallization zone rolling, with the deformation of each pass being 19% to 25% and the final rolling temperature being greater than the end austenitizing temperature; the second stage is two-phase zone rolling, with the deformation of each pass being 15% to 19% and the final rolling temperature being greater than the start austenitizing temperature.

[0013] 3) After rolling, intercritical annealing is performed, followed by water cooling to room temperature to obtain hot-rolled medium and thick plates.

[0014] Furthermore, the holding temperature in step 1) and the content of C-Al-Mn should conform to the formula

[0015]

[0016] Furthermore, in step 2), the temperature range of the two-phase region is a temperature range between the start austenitizing temperature and the end austenitizing temperature ≥ 300°C.

[0017] Furthermore, the critical annealing time in step 3) is 100 to 2000 seconds.

[0018] Furthermore, the critical annealing temperature and the C-Al-Mn content in step 3) should comply with the formula

[0019] Furthermore, the hot-rolled medium and thick plate in step 3) has a thickness of 8 to 28 mm, and the microstructure of the hot-rolled medium and thick plate is a layered heterogeneous structure of ferrite + martensite.

[0020] Furthermore, the hot-rolled medium and thick plate in step 3) is subjected to critical annealing to achieve an optimal ratio of ferrite and martensite phases, and the optimal ratio of the two phases is 1:1.

[0021] The medium and thick plate of the present invention is suitable for ship and marine engineering structure steel.

[0022] Features and advantages of the present invention:

[0023] 1. Through composition design, low-density steel with a two-phase temperature range of ≥300°C is obtained, which breaks through the current situation of traditional low-alloy steel where the critical process is difficult to achieve and control due to the small two-phase region.

[0024] 2. Through two-stage multi-pass rolling in the high-temperature recrystallization zone and the two-phase zone, a layered heterogeneous structure with a microstructure of ferrite + martensite is obtained. The heterogeneous structure design enables the material to deform in a coordinated manner when subjected to external force, reduces stress concentration, and significantly improves the strength and toughness of the material.

[0025] 3. By adjusting the ratio of the two phases through critical annealing in the two-phase region, the comprehensive mechanical properties are optimized. The yield strength of the hot-rolled plate is greater than 690MPa, the tensile strength is greater than 890MPa, the elongation after fracture is greater than 40%, and the transverse V-mouth Charpy impact energy at -100℃ is greater than 220J (continuous).

[0026] 4. The low Mn content design effectively reduces the Mn volatilization and Mn element segregation during the welding process, reduces the welding difficulty, saves production costs, reduces environmental pollution, and improves the organizational uniformity of the welding area.

[0027] This invention breaks through the limitations of traditional high manganese designs to improve low-temperature impact performance, significantly improving the low-temperature impact toughness of steel while achieving excellent overall performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a microstructure photograph of Example 1, which has a layered heterogeneous structure of ferrite + martensite. DETAILED DESCRIPTION

[0029] In order to express the content of the present invention more clearly, further description is given below in conjunction with preferred embodiments. Those skilled in the art should understand that the specific content described below is non-limiting but illustrative, and should not be used to limit the scope of protection of the present invention.

[0030] According to the chemical composition design of the present invention, various components are added into a vacuum melting furnace for melting, and when the solution temperature reaches above 1560° C., the solution is taken out of the furnace for pouring, and when the solution is cooled to room temperature, the chemical composition is analyzed. The chemical composition results are shown in Table 1.

[0031] Table 1 Composition and two-phase temperature of the experimental steel of the present invention (wt.%)

[0032]

[0033] Example 1

[0034] After casting the alloy of Scheme 1, it was kept at a homogenization temperature of 1210°C for 130 minutes for homogenization treatment, and then rolled at 1180°C. The rolling was divided into two stages. The first stage was high-temperature recrystallization zone rolling: 4 passes, with pass reduction rates of 24.6%, 21.5%, 20.3%, and 19.3%, respectively, and the pass interval was no more than 18s. The final rolling temperature was 1120°C; the second stage was two-phase zone rolling: 5 passes, with pass reduction rates of 18.2%, 18.8%, 17.9%, and 17.9%, respectively, and the pass interval was no more than 18s. The final rolling temperature was 823°C, and the post-rolling annealing was 300s, the annealing temperature was 776°C, and then water-cooled to room temperature. The final thickness of the steel plate is 11mm, and its microstructure is a heterogeneous structure of dual-phase layered ferrite + martensite ( Figure 1 shown).

[0035] Example 2

[0036] After casting the alloy of Scheme 2, it was kept at a homogenization temperature of 1224°C for 130 minutes for homogenization treatment, and then rolled at 1220°C. The rolling was divided into two stages. The first stage was high-temperature recrystallization zone rolling: 4 passes, the pass reduction rates were 23.6%, 21.5%, 2.3%, and 19.5%, the pass interval was no more than 18s, and the final rolling temperature was 1120°C; the second stage was two-phase zone rolling: 5 passes, the pass reduction rates were 17.8%, 17.2%, 17.5%, and 17.1%, the pass interval was no more than 18s, the final rolling temperature was 843°C, and the post-rolling annealing was 300s, the annealing temperature was 760°C, and then water-cooled to room temperature. The final thickness of the steel plate is 13mm, and its organization is a heterogeneous structure of dual-phase lamellar ferrite + martensite.

[0037] Example 3

[0038] After casting the alloy of Scheme 3, it was kept at a homogenization temperature of 1221°C for 130 minutes for homogenization treatment, and then rolled at 1160°C. The rolling was divided into two stages. The first stage was high temperature recrystallization zone rolling: 4 passes, the pass reduction rates were 21.3%, 20.1%, 20.3%, and 19.1%, the pass interval was no more than 18s, and the final rolling temperature was 1100°C; the second stage was two-phase zone rolling: 5 passes, the pass reduction rates were 17.3%, 15.8%, 16.9%, and 15.9%, the pass interval was no more than 18s, the final rolling temperature was 773°C, and the post-rolling annealing was 300s, the annealing temperature was 780°C, and then water-cooled to room temperature. The final thickness of the steel plate is 16mm, and its organization is a heterogeneous structure of dual-phase lamellar ferrite + martensite.

[0039] Table 2 Mechanical properties of steel samples of different schemes

[0040]

[0041] Table 3 Corrosion resistance of the embodiments of the present invention, corrosion rate g / m 2 h(Test standard GB / T17897-2016)

[0042]

[0043] The corrosion resistance of the medium and thick plate obtained in this embodiment in a high Cl ion environment is more than 2.2 times that of USU series stainless steel.

[0044] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A super-tough low-density steel medium and thick plate, characterized in that: Its chemical composition is recorded by weight percentage as C: 0.008-0.33%, Al: 1.5-5.5%, Mn: 0.6-5.5%, Cr: 0.01-3.6%, Ti: 0.0015-0.32%, and the content of C, Al, and Mn elements meets 0.7≤Mn+Cr≤8.3, the rest are Fe and unavoidable impurities; the rolling is divided into two stages and multiple passes, each stage has 3 to 5 passes, the pass interval is not more than 18s, the deformation amount of each pass in the first stage is 19% to 25%, and the final rolling temperature is greater than the end austenitizing temperature; the deformation amount of each pass in the second stage is 15% to 19%, and the final rolling temperature is greater than the start austenitizing temperature. Critical annealing is carried out after hot rolling to obtain hot-rolled medium and thick plates.

2. The ultra-tough low-density steel medium and thick plate according to claim 1, characterized in that: Its chemical composition is recorded by weight percentage as C: 0.009-0.31%, Al: 1.7-5.3%, Mn: 0.7-5.2%, Cr: 0.02-3.5%, Ti: 0.0018-0.31%, and the content of C, Al, and Mn elements meets 0.7≤Mn+Cr≤8.3, the rest are Fe and unavoidable impurities.

3. The method for preparing the ultra-tough low-density steel medium and thick plate according to claim 1 or 2, characterized in that: The specific steps are as follows: 1) Melting according to the alloy composition ratio, the ingot is kept at 1190-1260℃ for 90-300min for homogenization treatment, and then rolling is started above the austenitizing end temperature; 2) The rolling is divided into two stages and multiple passes, with 3 to 5 passes in each stage and the interval between passes not more than 18s. The first stage is high temperature recrystallization zone rolling, with a deformation of 19% to 25% in each pass and a final rolling temperature greater than the end austenitizing temperature; the second stage is two-phase zone rolling, with a deformation of 15% to 19% in each pass and a final rolling temperature greater than the start austenitizing temperature; 3) After rolling, intercritical annealing is performed, followed by water cooling to room temperature to obtain hot-rolled medium and thick plates.

4. The method for preparing the ultra-tough low-density steel medium and thick plate according to claim 3, characterized in that: Step 1) The holding temperature and the content of C-Al-Mn should conform to the formula 5. The method for preparing the ultra-tough low-density steel medium and thick plate according to claim 3, characterized in that: In step 2), the temperature range of the two-phase region is the temperature range between the start austenitizing temperature and the end austenitizing temperature ≥ 300°C.

6. The method for preparing the ultra-tough low-density steel medium and thick plate according to claim 3, characterized in that: The critical annealing time in step 3) is 100 to 2000 seconds.

7. The method for preparing ultra-tough low-density steel medium and thick plates according to claim 3, characterized in that: The critical annealing temperature and the C-Al-Mn content in step 3) should meet the formula 8. The method for preparing ultra-tough low-density steel medium and thick plates according to claim 3, characterized in that: The hot-rolled medium and thick plate in step 3) has a thickness of 8 to 28 mm, and the microstructure of the hot-rolled medium and thick plate is a layered heterogeneous structure of ferrite + martensite.

9. The method for preparing ultra-tough low-density steel medium and thick plates according to claim 3, characterized in that: The hot rolled medium and thick plate in step 3) is subjected to critical annealing to achieve a ferrite-martensite phase ratio of 1:

1.

10. The ultra-tough low-density steel medium and thick plate according to claim 1 or 2 is suitable for use as steel for ship and marine engineering structures.

Citation Information

Patent Citations

  • Super strength C-Al-Mn-Si series low-density steel and its preparation method

    CN103820735A

  • Preparation method for low-density steel with strength and elongation product larger than 50 GPa.%

    CN107674955A

  • Ageing strengthening high-toughness light steel and manufacturing method thereof

    CN114807772A

  • Dispersion delta phase strengthened low-density high-toughness steel and manufacturing method thereof

    CN114875318A

Cited By

  • High-yield-strength bar and preparation method thereof

    CN120330599A